2015
DOI: 10.1039/c5sm01089f
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and structural comparison between primary tumor and lymph node metastasis cells in colorectal cancer

Abstract: SW480 and SW620 colon carcinoma cell lines derive from primary tumour and lymph-node metastasis of the same patient, respectively. For this reason, these cells represent an ideal system to analyse phenotypic variations associated with the metastatic process. In this study we analysed SW480 and SW620 cytoskeleton remodelling by measuring the cells' mechanics and morphological properties using different microscopic techniques. We observed that different specialized functions of cells, i.e. the capacity to metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
60
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 39 publications
9
60
1
Order By: Relevance
“…In the case of ovarian cancer, cells are softer with greater migration and invasion abilities as compared to healthy ovarian cells [42]. The same trend has been observed in other cancer types such as cervical and colorectal [9,27]. Overall, it has been shown that in most cancer types, cancer cells are generally more deformable than their normal counter parts [19,41].…”
Section: Introductionsupporting
confidence: 59%
“…In the case of ovarian cancer, cells are softer with greater migration and invasion abilities as compared to healthy ovarian cells [42]. The same trend has been observed in other cancer types such as cervical and colorectal [9,27]. Overall, it has been shown that in most cancer types, cancer cells are generally more deformable than their normal counter parts [19,41].…”
Section: Introductionsupporting
confidence: 59%
“…Samples for Scanning Electron Microscopy have been prepared as described elsewhere 28 with slight modifications. Briefly, hydrogels have been fixated in Glutaraldehyde solution (2.5%) for 2 hours and then dehydrated serially in ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Although these existing results about the correlation between cell stiffness and the capability of motility are contradictory, it is interesting to note that the data based on cell lines generated from normal and malignant tissues tended to be consistent that the more invasive cancer cells with a lower Young's modulus, except one group who observed an opposite result in a study on prostate cancer cells [13] and two papers concluding that there was no predictive correlation between motility and stiffness [14,15]. A large difference exists between the studies that assessed the stiffness of cells with modified motility through pharmacological treatment or genetic modification, and cells with higher motility were demonstrated to be softer [8][9][10][16][17][18][19], stiffer [20][21][22][23][24] or unaltered [15] in different studies.…”
Section: / 28mentioning
confidence: 85%
“…The commonly used method for analyzing the fluorescence of phalloidin staining fails to illustrate the diversity of spatial structures of actin filaments. Analysis of the coherency[14] or the fractal dimension[46] of actin filament performance on the confocal images can partly help to describe the spatial structures of actin filaments, and more novel analytical and experimental strategies should be encouraged to provide more information about the spatial structures of actin filaments and their correlation with cell stiffness and motility. Because there is great discrepancy on how the remodeling of actin filaments regulates cell stiffness, attention should be placed on how the spatial structures of the actin network impact cell stiffness in the near future.…”
mentioning
confidence: 99%